Use of aspirin and bleeding-related complications after hepatic resection. Issue 4 (7th February 2018) - Gelli, M.; Allard, M. A.; Farges, O.; Paugam-Burtz, C.; Mabrut, J. Y.; Regimbeau, J. M.; Vibert, E.; Boleslawski, E.; Adam, R.; Aussilhou, B.; Badaoui, R.; Bonnet, A.; et al.
Abstract: Background: The operative risk of hepatectomy under antiplatelet therapy is unknown. This study sought to assess the outcomes of elective hepatectomy performed with or without aspirin continuation in a well balanced matched cohort. Methods: Data were retrieved from a multicentre prospective observational study. Aspirin and control groups were compared by non-standardized methods and by propensity score (PS) matching analysis. The main outcome was severe (Dindo–Clavien grade IIIa or more) haemorrhage. Other outcomes analysed were intraoperative transfusion, overall haemorrhage, major morbidity, comprehensive complication index (CCI) score, thromboembolic complications, ischaemic complications and mortality. Results: Before matching, there were 118 patients in the aspirin group and 1685 in the control group. ASA fitness grade, cardiovascular disease, previous history of angina pectoris, angioplasty, diabetes, use of vitamin K antagonists, cirrhosis and type of hepatectomy were significantly different between the groups. After PS matching, 108 patients were included in each group. There were no statistically significant differences between the aspirin and control groups in severe haemorrhage (6·5 versus 5·6 per cent respectively; odds ratio (OR) 1·18, 95 per cent c.i. 0·38 to 3·62), intraoperative transfusion (23·4 versus 23·7 per cent; OR 0·98, 0·51 to 1·87), overall haemorrhage (10·2 versus 12·0 per cent; OR 0·83, 0·35 to 1·94), CCI score (24 versus 28; P = 0·520), major complications (23·1 versus 13·9 per cent; OR 1·82, 0·92 to 3·79) and 90-day mortality (5·6 versus 4·6 per cent; OR 1·21, 0·36 to 4·09). Conclusion: This observational study suggested that aspirin continuation is not associated with a higher rate of bleeding-related complications after elective hepatic surgery.